Data preparation, treatment and visualization for constructing holograms with the electron-beam installation ZBA-21 - Serezhnikov, S.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2002)
A program package was developed for the design and construction of computer-generated holograms with the aid of the technology based on electron-beam lithography (the installation ZBA-21 was used). The package allows one to visualize microreliefs prepared for exposition, to transform data from the raster format to the ZBA-format, and to form data sets for exposition of holograms from individual elements. The package is used at the Research Computing Center of Moscow State University to design computer-generated holograms.